Analisis Peran Penjagaan dan Patroli Laut dalam Meningkatkan Keselamatan Berlayar - M. Zaini; ⁠Frisca Maria (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Shipping safety is a crucial aspect in supporting maritime transportation activities, logistics distribution, and community mobility in Indonesian waters. The high intensity of shipping and various potential risks, such as ship accidents, maritime legal violations, and security disturbances, demand an effective surveillance system. Sea guarding and patrols are among the strategic efforts to create security, order, and safety in the waters. This study aims to analyze the role of sea guarding and patrols in improving shipping safety, identify the obstacles encountered, and examine the handling of violations and the support for surveillance facilities. The research employs a descriptive qualitative approach. Data were obtained through interviews, observations, and documentation with parties involved in sea guarding and patrol activities. Data analysis was conducted through stages of data reduction, data presentation, and conclusion drawing to obtain a comprehensive overview of the implementation of sea patrols and their contribution to shipping safety. The results show that sea guarding and patrols play an important role in vessel traffic monitoring, maritime law enforcement, protection of aquatic resources, and emergency response. The effectiveness of patrols is evident from increased compliance among sea users and reduced potential for violations and accidents. The obstacles encountered include the vastness of the waters, unpredictable weather conditions, limited patrol fleets, surveillance equipment, and human resources. Support from facilities such as patrol vessels, speed boats, radar, GPS, and communication radios is a key factor in supporting successful surveillance. Sea guarding and patrols contribute significantly to improving shipping safety. Strengthening facilities, enhancing personnel capacity, and optimizing inter-agency coordination are necessary to continuously improve the effectiveness of surveillance and security in the waters.